Absence of Increase in Carotid Artery Intima-Media Thickness in Infants of Diabetic Mothers - Atabek, Mehmet Emre (Galenos Publishing, 2011)

(untitled)
Objective: Infants of diabetic mothers (IDM) are considered as a risk group for atherosclerosis. Increased aortic intima-media thickness has been reported in IDM. The purpose of this study was to assess carotid artery intima-media thickness (CA-IMT), left ventricular mass index (LVMI) and atherosclerotic risk factors in IDM. Methods: Thirty IDM and 25 healthy controls were included in the study. Of these infants, 14 were appropriate-for-gestational age (AGA) and 16 were large-for-gestational age (LGA). CA-IMT and LVMI were obtained by M-mode echocardiographic examination. The relationship between parameters of atherosclerosis and echocardiographic measurements was assessed by Pearson’s correlation analysis. Results: LVMI was higher in LGA IDM when compared to AGA IDM and controls. CA-IMT was not significantly different between the groups and was also not related to atherosclerotic risk factors. Serum lipid and insulin levels were higher in LGA IDM when compared with AGA IDM and controls. There were no correlations between CA-IMT, LVMI and atherosclerotic risk factors. Conclusions: In contrast to previous reports indicating an increase in CA-IMT in IDM, no differences were found between IDM and controls in this study. Our results indicate that macrosomic IDM are prone to hypertrophic cardiomyopathy but not to atherosclerotic changes in the blood vessels. Conflict of interest:None declared.